Beyond rehabilitation: A prevention model of reserve and brain maintenance in multiple sclerosis. (September 2019) - Brandstadter, Rachel; Katz Sand, Ilana; Sumowski, James F
Persons with multiple sclerosis (MS) experience cognitive and physical decline despite more effective disease-modifying therapies (DMTs), and symptomatic treatments currently have limited efficacy. The best treatment of MS disability may, therefore, be prevention of decline. Here, we present a working model of reserve and brain maintenance, with a focus on modifiable risk and protective factors. At disease onset, patients have varying degrees of reserve, broadly conceptualized as the dynamic availability of cerebral resources to support functional capacity. A clinical focus on prevention aims to minimize factors that deplete reserve (e.g. disease burden, comorbidities) and maximize factors that preserve reserve (e.g. DMTs, cardiovascular health). We review evidence for cardiovascular health, diet, and sleep as three potentially important modifiable factors that may modulate cerebral reserve generally, but also in disease-specific ways. We frame the brain as a limited capacity system in which inefficient usage of available cerebral capacity (reserve) leads to or exacerbates functional deficits, and we provide examples of factors that may lead to such inefficiency (e.g. poor mood, obesity, cognitive-motor dual-tasking). Finally, we discuss the challenges and responsibilities of MS neurologists and patients in pursuing comprehensive brain maintenance as a preventive approach.